1989
DOI: 10.1103/physrevlett.63.916
|View full text |Cite
|
Sign up to set email alerts
|

Carr, Bloom, Petrovich, and Philpott reply

Abstract: Carr, Bloom, Petrovich, and Philpott Reply: Geesaman and Zeidman l have pointed out a deficiency in the double ratio (R-Rz/Rs) of isoscalar to isovector inelastic scattering strengths (Rz^Zo/Z?) and proton stripping spectroscopic strengths (Rs~Sp/Sp) predicted in our recent large-basis shell-model study 2 of stretched 6~ states in 28 Si as compared with experiment. This is a valid point which was inadequately discussed in our Letter; however, Geesaman and Zeidman also make comparisons with an earlier, more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 4 publications
1
22
1
Order By: Relevance
“…Measurements for the excitations however provide only a limited extension of the inelastic scattering results. At present, the most interesting aspect of the study of stretched configurations is the fragmentation of the strength [206]. Charge-exchange measurements have not contributed to such studies though, because of the relatively poor energy resolution available, about 300 keV for (p,n) measurements and 1 MeV for (n,p).…”
Section: Stretched Statesmentioning
confidence: 96%
See 1 more Smart Citation
“…Measurements for the excitations however provide only a limited extension of the inelastic scattering results. At present, the most interesting aspect of the study of stretched configurations is the fragmentation of the strength [206]. Charge-exchange measurements have not contributed to such studies though, because of the relatively poor energy resolution available, about 300 keV for (p,n) measurements and 1 MeV for (n,p).…”
Section: Stretched Statesmentioning
confidence: 96%
“…It was shown that although the 1p-1h configuration was unique, this was not an eigenstate of the nuclear Hamiltonian, so that the strength of the excitation was spread over other states by residual interactions. The cross section for excitation of a particular state however was proportional to the strength of the stretched configuration in the wave function of that state [206]. Thus the (e, e') reaction, involving the well understood electromagnetic interaction, may be used to determine the 1p-1h transition density; this may then be used in the analysis of (p,p') results to study the effective N-N interaction.…”
Section: Stretched Statesmentioning
confidence: 99%
“…14) of the total (f7/2d&iz) strength [7], the T = O, J = 6 state in Mg represents only 4.4% (Zo =0.044) of the total (f7/2d5/z) strength (see Table I). Recent large basis shell model calculations predict that the T=O, J =6 strength concentrated in the yrast state should be Z0=0.…”
Section: Compared Tomentioning
confidence: 99%
“…The theoretical Z coefficients are from the sum rules of Ref. [6] for the extreme-single-particle model (ESPM) and from the large basis shell model (LBSM) calculations of Carr [7,8]. The ratio between experiment and theory is defined as Mg, which is in strong disagreement with that from ana1ysis of recent proton scattering measurements [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation